The Shape and Shaping of Isaiah and Psalms as Books in the Zion Tradition - Abernethy, Andrew T. (The catholic biblical quarterly, 2024)
This article identifies parallels between methods and conceptual impulses that informed the shape and shaping of MT Psalms and MT Isaiah as books. For the past fifty years, there has been abundant interest in the macrostructures of the Psalter (MT) and Isaiah, yet inquiry into the shape and shaping of these two books has taken place in isolation from one another. When compared, there is striking overlap between the shapes of MT Psalms and MT Isaiah. In this article, I show similarities between Psalms and Isaiah in terms of both editorial methods (dual introductions; central hinges) and semantic emphases (torah observance; the nations; divine kingship in Zion; worship) that give shape to each book. Consequently, scholarship can move beyond simply acknowledging commonality between individual texts in the Psalter and Isaiah. A remarkable level of similarity between Psalms and Isaiah as books exposes how a common set of theological instincts from the Zion tradition informed how these books took form.